Exploring dementia care for community-dwelling older adults in Thailand: A qualitative descriptive study - Mongklam, Parichat; Kraithaworn, Phachongchit; Piyatrakul, Sangduen (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Dementia is a growing public health concern in Thailand, placing significant demands on families, communities, and the healthcare system. Despite national policies supporting integrated care, community-based dementia services face challenges related to resource limitations, caregiver burden, and access to training. Objective: This study aimed to explore the delivery of dementia care for community-dwelling older adults in Thailand, focusing on care processes, challenges, and support systems from the perspectives of community health nurses (CHNs), village health volunteers (VHVs), and family caregivers. Methods: A qualitative descriptive approach was used. Twenty-two participants, including CHNs, VHVs, and family caregivers, were purposively selected from a metropolitan district in Thailand. Data were collected through semi-structured interviews and focus group discussions, supplemented by contextual health assessments. Thematic analysis was conducted using Sandelowski’s content analysis framework, with rigor ensured through member checking, audit trails, and peer debriefing. Results: Six categories emerged: 1) Care processes involved integrated services across prevention, promotion, treatment, and rehabilitation, with family playing a central role; 2) Conditional factors included strong cultural values of filial responsibility and provider-community trust; 3) Care outcomes reflected partial independence in older adults, with caregivers experiencing varying levels of well-being and frequent stress due to lack of support and training; 4) Successes were attributed to supportive policies, family dedication, and healthcare providers’ intrinsic motivation; 5) Barriers included staff shortages, caregiver health issues, limited training, and insufficient confidence in VHVs; 6) Model development emphasized the need for policy backing, multidisciplinary collaboration, caregiver capacity-building, and dementia-specific community services. Conclusion: Community-based dementia care in Thailand is driven by cultural commitment and dedicated local health workers but hindered by systemic constraints. Strengthening caregiver education, expanding service networks, and enhancing integrated support systems are critical for improving care quality and reducing caregiver burden. Equipping CHNs and VHVs with dementia-specific training and supporting their role in caregiver education and interdisciplinary coordination can further enhance the effectiveness and sustainability of dementia care in community settings.